Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1542/peds.2014-1677
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Bilirubin After Phototherapy in Term and Preterm Infants

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Phototherapy decreases bilirubin concentration in skin more rapidly than in blood. During and after phototherapy, transcutaneous bilirubin measurements are considered unreliable and therefore discouraged. WHAT THIS STUDY ADDS:Transcutaneous bilirubin underestimates total serum bilirubin by 2.4 mg/dL (SD, 2.1 mg/dL) during the first 8 hours after phototherapy. This gives a safety margin of ∼7 mg/dL below the treatment threshold to omit confirmatory blood sampling. abstract OBJECTIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…[4][5][6][7][8] Tan and Dong 9 referred a study group consisting exclusively of Asian infants. Grabenhenrich et al 10 included only 39 term infants, and Povaluk et al 11 from Brazil only 15 term neonates after phototherapy. The findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Tan and Dong 9 referred a study group consisting exclusively of Asian infants. Grabenhenrich et al 10 included only 39 term infants, and Povaluk et al 11 from Brazil only 15 term neonates after phototherapy. The findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Juster‐Reicher et al found a good correlation between TcB and TSB at 8 hours after phototherapy in infants with ≥35 weeks of gestational age and birth weight of ≥2000 g . Other investigators found a moderate correlation between TcB and TSB before and after phototherapy, but a lesser correlation during phototherapy; moreover, some studies found that TcB was not reliable for monitoring neonatal hyperbilirubinemia during or after phototherapy . In this study, we demonstrated the correlation between TcB and TSB before, under (mean duration under phototherapy was 3.7 and 4.4 days in term and late‐preterm infants, respectively), and after discontinuing phototherapy in a population of jaundiced term and late‐preterm infants, which revealed acceptably a highly positive linear correlation.…”
Section: Discussionmentioning
confidence: 45%
“…[18][19] Bilirubinometer transkutan merupakan metode yang akurat dan tidak invasif sehingga dapat menjadi alternatif pemeriksaan bilirubin neonatus. 20 Kelemahan [21][22] Beberapa penelitian melaporkan hasil pemeriksaan bilirubin yang tidak akurat dan konsisten apabila bilirubin total lebih besar dari 15mg/dl. 14,23,24 Dengan demikian, secara umum TcB cukup menjanjikan karena meminimalisir pengambilan darah, dapat digunakan sebagai pemeriksaan universal, dan tetap akurat dengan kadar bilirubin di bawah 15mg/dl.…”
Section: Pemeriksaan Bilirubin Non-invasifunclassified